Safety of treatment of uterine fibroids with the selective progesterone receptor modulator, ulipristal acetate - Jacques Donnez; Olivier Donnez; Marie-Madeleine Dolmans (Publishing House TRILIST, 2017)
Introduction: During the last decade, there has been increased emphasis on the role of progesterone in the promotion of fibroid growth, as well as heightened interest in modulating progesterone pathways by use of selective progesterone receptor modulators. Among them, ulipristal acetate (UPA) has proved its efficacy in the management of symptomatic myomas by controlling bleeding and inducing amenorrhea, and reducing the size of myomas in the majority of cases. Areas covered: In this review, we summarize published scientific studies exploring evidence of the safety of selective progesterone receptor modulators and particularly UPA, a drug approved for the management of symptomatic uterine fibroids. We focus essentially on endometrial changes induced by UPA, and also evaluate other safety outcomes. Expert opinion: Data from published reports of randomized controlled trials over 5 years have demonstrated that UPA does indeed induce endometrial changes (known as progesterone receptor modulator-associated endometrial changes), but they have been shown to be both benign and reversible. Novel algorithms published very recently provide an extensive overview that may be considered as the latest expert opinion. Thus, in infertile women of reproductive age, two courses of 3 months of UPA are recommended in case of type 2 myomas or multiple myomas distorting the uterine cavity. Subsequent therapy is determined depending on the response and restoration of the uterine cavity. If there is no desire for pregnancy, long-term (four courses) intermittent therapy may be initiated. In case of a good response, treatment is stopped and restarted only if symptoms recur. In premenopausal women wishing to preserve their uterus, four courses of 3 months is the proposed strategy. Contraindications to prescribing UPA include pregnancy, breastfeeding, genital bleeding of unknown etiology of origin other than uterine fibroids, and presence of uterine, cervical, ovarian, or breast cancer.